ПЕДАГОГІЧНІ УМОВИ ФОРМУВАННЯ ПЕДАГОГІЧНОЇ КУЛЬТУРИ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2010)
In article pedagogical conditions of formation pedagogical culture of the student higher educational institution are considered during training.